Validation of associations for the temporary ponds of the class Isoeto-Nanojuncetea in Puglia (southern Italy) - Tomaselli, Valeria; Beccarisi, Leonardo; Cambria, Salvatore; Forte, Luigi; Minissale, Pietro; Sciandrello, Saverio; Veronico, Giuseppe; Brullo, Salvatore (Mediterranean Botany, 2022)
This paper presents the validation of 16 new associations, described in a previous contribution, for the temporary ponds of the class Isoeto-Nanojuncetea in Apulia (southern Italy).